The Effects of using Stepped Cascade Aeration and Multimedia Filter System for Iron Removal in Groundwater - Z Radzi, E; S Wahab, M.; Z Sahdan, M; Hamdan, R; A Raus, A (International Journal of Engineering and Technology, 2019)
Tahfiz school is an alternative education system for Muslims in Malaysia. Most of the traditional tahfiz school have been modernized and technologically well-equipped. However, they always have issues with water supply because most tahfiz schools are located in remote areas. Hence, an access to groundwater is provided to the school. A study was done by using groundwater samples taken from Sekolah Menengah Islam Darul Bayan, Paka, Terengganu and its recorded high amount of iron which is 13.7 mg/L. The iron value is exceeded the raw water standard of 1.0 mg/L, thus affecting its quality and it is not safe for domestic purpose. In this work, two methods of iron removal have been studied using stepped cascade aeration design and multimedia filter system. Using the stepped cascade aeration, the amount of removed iron content is 1.6 mg/L hence lowering its value to 12.1 mg/L with 11.67% removal. Meanwhile, the multimedia filter system is able to remove 12.7 mg/L, hence making its value to 1.0 mg/L with 92.7% removal. Therefore, the usage of stepped cascade aeration for groundwater with iron content less than 2.0 mg/L is sufficient. Whereas, the usage of multimedia filter system is needed for groundwater with iron content more than 2.0 mg/L.Â Â